Efektifitas Pemberian Edukasi Pengetahuan Penanggulangan Bencana pada Pelajar SMA Negeri 07 Kabupaten Sarolangun - Elfina, Titi Dwi; Subandi, Andi; Rudini, Dini (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2021)
The number of disaster events cannot be separated from the role of the community. This study aims to determine the value of students pretest and posttest knowledge in flood and landslide disaster management and analyze the provision of education after and after providing disaster management education. The method used is quasi-experimental with a pretest and posttest with control approach. The research was conducted by giving different treatment to two groups. This research was conducted at SMA Negeri 07, Sarolangun Regency, using class XII IPA II. The sample used in 1 science class was 33 students. Sampling using simple random sampling method. The results show that there is a significant difference between pretest and posttest knowledge of disaster management in floods and landslides in Sarolangun district. The value obtained in the pretest the average level of knowledge is 64.64 and the protest value is the average level of knowledge is 81.32. The results of the t-test in the first stage, namely the pretest, obtained a sing value (2 tailed) of 0.00, namely <0.05, with Thus, it can be concluded that there is a significant (significant) difference in the results of the science class pretest, the results of the t-test value at the posttest stage of the sing value (2 tailed as 0.111 that is > 0.05. Thus it can be concluded that there is no significant difference (significant) between posttest and pretest results. Value pretest 64.64, with the result the percentage > 70% can be said to be less.